Analysis of Production Cost of Tempe Using the Full Costing Method in Tempe Asli HB Jambi Agroindustry: Analisis Harga Pokok Produksi Tempe dengan Metode Full Costing pada Agroindustri Tempe Asli HB Jambi - Rahmi Fauziah, Adinda; Damayanti, Yusma; Sri Nurchaini, Dewi (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2024)
This research aims to: 1) Describe the overview of the Asli HB Jambi tempe agroindustry, 2) Analyze the calculation of tempe production costs based on the agroindustry and the full costing method, 3) Analyze the selling price of tempe based on the agroindustry and the cost lus Pricing method, 4) Analyze the impact of imported soybean price fluctuations on the cost of tempe production at Asli HB Jambi. The analytical method used is quantitative descriptive analysis, with full costing calculation, cost plus pricing, and paired t-test analysis as the analytical tools. Based on the analysis, the results are: 1) The Asli HB Jambi tempe agroindustry is a small-scale individual industry producing 250 gram packaged tempe, processing an average of 1,092 kg of soybeans per cycle. Marketing is done through three channels: a) agroindustry-consumer, b) agroindustry-reseller-consumer, c) agroindustry-sales-reseller-consumer. 2) The production cost per 250 grams is IDR 2,358.68 based on agroindustry calculations and IDR 2,409.59 using the Full Costing method. After marketing adjustments, the Full Costing production cost rises to IDR 2,471.34 due to unsold tempe returns. 3) The agroindustry's selling prices are IDR 4,500 (Channel I), IDR 4,000 (Channel II), and IDR 3,500 (Channel III), while the Cost Plus Pricing method results in IDR 4,631, IDR 4,149, and IDR 3,667, respectively. 4) A 10% change in imported soybean prices significantly affects production costs, increasing to IDR 2,602.66 when imported soybean prices rise and decreasing to IDR 2,216.53 when imported soybean prices fall.